An analysis of paediatric clinical presentations in Northwest Syria and the effect of forced displacement, 2018–2022 - Vinay Kampalath; Ms Maia C. Tarnas; Ms Vaibhavee Patel; Mohamed Hamze; Randa Loutfi; Bachir Tajaldin; Ahmad Albik; Ayman Kassas; Anas Khashata; Aula Abbara (Global Epidemiology)
Background: One in six children worldwide lives in a region exposed to armed conflict. In conflicts, children are among the most vulnerable, and at risk of adverse health outcomes. We sought to describe trends in child and adolescent morbidity in northwest Syria (NWS) and understand how forced displacement affects clinical utilisation during the Syrian conflict. Methods: Retrospective data between January 2018 and December 2022 were obtained from the Syrian American Medical Society (SAMS), a non-governmental organisation that operates health facilities in NWS. After initial descriptive analyses were completed, we performed a seasonal-trend decomposition to estimate the seasonality of clinical presentations. We subsequently employed a multivariate regression model incorporating age, gender, residency status, season, and a random district-level intercept to measure the association between the odds of clinical consultation and forced displacement. Findings: Across 51 reporting SAMS facilities, 2,687,807 clinical consultations were studied over a five-year period. Seasonality was demonstrated for every clinical consultation category. Higher levels of forced displacement were associated with increased odds of consultations for nutrition, trauma, NCDs and mental health and decreased odds of consultation for communicable diseases. Aside from traumatic injury, internally displaced persons (IDPs) had higher AORs of clinical consultations compared to host populations. Interpretation: Forced displacement differentially impacts clinical utilisation among children in northwest Syria, and the effects of displacement persist for at least six months. Clinical needs vary by host/IDP status, sex, age, and season. This study can assist policymakers in forecasting the health needs of children in northwest Syria.